Toward a Theory of Social Practices: A Development in Culturalist Theorizing - Reckwitz, Andreas (European journal of social theory, 2002)
This article works out the main characteristics of `practice theory', a type of social theory which has been sketched by such authors as Bourdieu, Giddens, Taylor, late Foucault and others. Practice theory is presented as a conceptual alternative to other forms of social and cultural theory, above all to culturalist mentalism, textualism and intersubjectivism. The article shows how practice theory and the three other cultural-theoretical vocabularies differ in their localization of the social and in their conceptualization of the body, mind, things, knowledge, discourse, structure/process and the agent.